Reflections on violence - Sorel, Georges 1847-1922 (Cambridge University Press, 1999)
Georges Sorel's Reflections on Violence is one of the most controversial books of the twentieth century: J. B. Priestley argued that if one could grasp why a retired civil servant had written such a book then the modern age could be understood. It heralded the political turmoil of the decades that were to follow its publication and provided inspiration for Marxists and Fascists alike. Developing the ideas of violence, myth and the general strike, Sorel celebrates the heroic action of the proletariat as a means of saving the modern world from decadence and of re-invigorating the capitalist spirit of a timid bourgeoisie. This edition of Sorel's classic text is accompanied by an editor's introduction by Jeremy Jennings, a leading scholar of political thought, both setting the work in its context and explaining its major themes. A chronology of Sorel's life and a list of further reading are included
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sorel, Georges -- 1847-1922; Syndicalism; Strikes and lockouts; Social conflict; Violence; Gewalt; Streik; Ethik; Politik; Syndikalismus; Klassenkampf